Student Use of Audio, Video, and Written Teacher Feedback: The Predictive Utility of Learning Modality Preference, Self-Regulated Learning, and Learning Style - Johnson, Genevieve; Cooke, Audrey (2015)
Students (n = 102) enrolled in a university course completed an online questionnaire that assessed three learning characteristics: 1) learning modality preference, 2) self-regulated learning, and 3) learning style as well as actual use of three types of feedback provided by their teachers during the study period (i.e., video, audio, and written). Student characteristics (i.e., independent variables) predicted use of video, audio, and written university teacher feedback. For example, students who preferred to receive information kinaesthetically (i.e., by doing rather than watching or listening) tended to prefer video feedback. Such results suggest a complex pattern of relationships between student psychoeducational characteristics and use of various forms of teacher feedback. Given the importance of teacher feedback to student learning, a variety of formats may best meet the learning needs of all university students.